Tillage method and glyphosate‐resistant alfalfa termination timing affect soil properties and subsequent corn yield. (9th December 2020) - Clark, Jason D.; Yost, Matt A.; Cardon, Grant E.; Ransom, Corey V.; Creech, J. Earl
Abstract: Application of glyphosate [N‐(phosphonomethyl) glycine]‐containing herbicides and tillage, alone or in combination, has been the standard for removing declining alfalfa ( Medicago sativa L.) stands. With glyphosate no longer an option to control glyphosate‐resistant alfalfa, different termination strategies are needed. Field studies across four site‐years in Utah evaluated the effect of tillage type and timing (fall conventional till, spring conventional till, fall strip‐till, spring strip‐till, and no‐till) and herbicide timing (fall, spring, in‐crop, and no herbicide) of 2, 4‐D (2, 4‐dichlorophenoxyacetic acid) and dicamba (3, 6‐dichloro‐2‐methoxybenzoic acid) on penetration resistance, alfalfa regrowth, corn ( Zea mays L.) emergence rate, and silage corn yield. Across tillage treatments, fall, spring, and in‐crop herbicide timings compared with no herbicide reduced alfalfa stem count and biomass by at least 74 and 92%, respectively. Emergence rate was greatest under fall and spring conventional till or spring strip‐till compared with fall strip‐till or no‐till. Silage corn yield was greatest and similar with fall or spring herbicide applications for all tillage systems and conventional tillage with an in‐crop herbicide application (19–27 Mg ha −1 ), followed by in‐crop herbicide application for conservation tillage systems and fall and spring conventional till without herbicide application (14–20 Mg ha −1 ), and lastly when only conservation tillage was used to terminate alfalfa (5–15 Mg ha −1 ). Silage corn yield can be optimized when glyphosate‐resistant alfalfa is terminated with herbicides prior to planting, regardless of tillage type or timing. Termination of glyphosate‐resistant alfalfa by herbicides after corn emergence, depending on tillage, reduces silage corn yield 9–19%. Core Ideas: Herbicides alone or combined with tillage adequately controlled glyphosate‐resistant alfalfa. Corn emerged faster with conventional‐till or spring strip‐till than with fall strip‐till or no‐till. Corn yield was similar regardless of tillage when herbicides were applied before corn planting. Terminating alfalfa with herbicides after corn emergence reduced silage corn yield.